(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Colorism, a discrimination against individuals based on their skin color. It remains an under-researched social problem in the South Asian region, particularly in countries like Pakistan, India, and Bangladesh. This silent bias shape one’s social acceptance and identity, education, and career opportunities. Despite its significance, this topic has received limited attention in Pakistani research. Methodology In order to analyze the impact of colorism on self-perception and confidence along social dimensions, a cross-sectional online survey was conducted with over 385 residents from Karachi, Pakistan. The questionnaire is designed in a way to cover the insights across four key domains: socio-demographic information, including age and grade level, as well as socioeconomic status, like income or occupation; self-esteem; and self-efficacy. Assessed through carefully constructed sets of assertive/ non-assertive items, participants’ perceptions about their skin tone worth together with capabilities were evaluated for endorsement at varying levels of confidence. Results The findings highlight the widespread yet unspoken influence of colorism on societal views and personal confidence within Pakistani society. Although many participants reported denying the role of skin tone they possess, deep-rooted skin tone biases do exist. Of the 385 respondents, 58.4% were female and 41.6% male, with 34% identifying as having a brown complexion. A majority (74.1%) of being under the age of 30 were socially active as well as vulnerable, as this age group is more exposed to societal standards of beauty and success, making them particularly susceptible to the psychological impacts of colorism. While 53.8% of participants reported that skin tone does not affect social relations, a significant proportion of 23.6% recognized its effect, while another 22.6% remained neutral, demonstrating some degree of internalized colorism. Regarding employment, only 19.2% believed their skin color had a negative impact on job prospects compared to 62.6% who disagreed, and the remainder (18.2%) were uncertain—regardless, these attitudes reveal persistent undertones of colorism in society. Further analysis using the Chi-square test showed that beliefs about career-related colorism significantly correlated with efforts to reduce or alter one’s skin tone, illustrating the psychological and behavioral impacts of such discrimination. Conclusion: The study highlights that perceptions of skin tone can influence social and interpersonal lives. It underscores the need for further research on colorism in the region to understand its implications better and promote discussion on this critical issue. BJMS, Vol. 25 No. 01 January’26 Page : 169-175